Procedural approaches and angiographic signs predicting first-pass recanalization in patients treated with mechanical thrombectomy for acute ischaemic stroke - Tomasello, Alejandro (Interv Neuroradiol, 2019)
BACKGROUND: First-pass recanalization via mechanical thrombectomy (MT) has been associated with improved clinical outcome in patients with acute ischaemic stroke. The optimal approach to achieve first-pass effect (FPE) remains unclear. No study has evaluated angiographic features associated with the achievement of FPE. We aimed to determine the procedural approaches and angiographic signs that may predict FPE. METHODS: We performed a prospective, multi-centre, observational study of FPE in patients with anterior circulation stroke treated with MT between February and June 2017. MTs were performed using different devices, deployment manoeuvres (standard versus ‘Push and Fluff’ technique), proximal balloon guide catheter (PBGC), distal aspiration catheter (DAC) or both. The angiographic clot protrusion sign (ACPS) was recorded. Completed FPE (cFPE) was defined as a modified thrombolysis in cerebral infarction score of 2c–3. Associations were sought between cFPE and procedural approaches and angiographic signs. RESULTS: A total of 193 patients were included. cFPE was achieved in 74 (38.3%) patients. The use of the push and fluff technique (odds ratio (OR) 3.45, 95% confidence interval (CI): 1.28–9.29, p = 0.010), PBGC (OR 3.81, 95% CI: 1.41–10.22, p = 0.008) and ACPS (OR 4.71, 95% CI: 1.78–12.44, p = 0.002) were independently associated with cFPE. Concurrence of these three variables led to cFPE in 82 vs 35% of the remaining cases (p = 0.002). CONCLUSIONS: The concurrence of the PBGC, the push and fluff technique, and the ACPS was associated with the highest rates of cFPE. Appropriate selection of the thrombectomy device and deployment technique may lead to better procedural outcomes. ACPS could be used to assess clot integration strategies in future trials.